Zinc Supplementation for Non-alcoholic Fatty Liver Disease: Literature Review - Trisha Anindya (Newinera Publisher, 2025)
Non-Alcoholic Fatty Liver Disease (NAFLD) is closely associated with several metabolic factors, including dyslipidemia, insulin resistance, obesity, oxidative stress, and elevated inflammatory markers. NAFLD is also one of the most common liver diseases, in which zinc deficiency plays a key role in its pathogenesis. Zinc supplementation has been evaluated as a potential adjunctive therapy to improve clinical outcomes in patients with NAFLD. This literature review aims to discuss the possible role of zinc supplementation as an adjuvant therapy in patients with NAFLD, based on current research findings, and to contribute to the existing scientific literature.